The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/1060028014543795
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Reduce Medication Errors in Pediatric Intensive Care

Abstract: Objective: To systematically examine the research literature to identify which interventions reduce medication errors in pediatric intensive care units. Data Sources: Databases were searched from inception to April 2014. Study Selection and Data Extraction: Studies were included if they involved the conduct of an intervention with the intent of reducing medication errors. Data Synthesis: In all, 34 relevant articles were identified. Apart from 1 study, all involved single-arm, before-and-after designs without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 51 publications
1
47
0
Order By: Relevance
“…, Manias et al . ) used quantitative pooling methods and, therefore, results were presented in the narrative form.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, Manias et al . ) used quantitative pooling methods and, therefore, results were presented in the narrative form.…”
Section: Resultsmentioning
confidence: 99%
“…, Manias et al . , Raban & Westbrook ) that examined the impact of the checklist, protocols and guidelines on medication administration processes. Checklists, in the form of simple paper reminders posted on medical charts or complex computerised reminders, are commonly used to prompt clinicians to remember to perform critical tasks.…”
Section: Resultsmentioning
confidence: 99%
“…Two previous systematic reviews investigated the impact of interventions to reduce medication errors in children, but did not discuss the fact that many of the studies included were of low quality . This systematic review critically described and assessed the quality of the published literature.…”
Section: Resultsmentioning
confidence: 99%
“…Weight‐based infusions have been shown to be prone to error, with 27% of infusion orders found to contain a prescribing error and 65% of prepared infusions being >10% variant from the prescribed concentration . By introducing SCI both of these error modes can be reduced by 50% or more …”
Section: Discussionmentioning
confidence: 99%
“…This then leads to the consideration of the systems in use to support the use of SCI. A recent systematic review identified that intravenous systems were effective at reducing medication errors by almost two‐thirds (RR 0.37, 95% CI 0.19–0.73) where these systems were suites of interventions including SCIs and ‘smart’ pumps and SCs being prepared centrally . In this study, 51% of respondents report using ‘smart’ pump technology, and 10% report using computerised infusion rate calculators.…”
Section: Discussionmentioning
confidence: 99%